Burkholderia gladioli strain KJ-34 exhibits broad-spectrum antifungal activity - Yang, Chunnan; Wang, Zhihui; Wan, Jiangxue; Qi, Tuo; Zou, Lijuan (Frontiers in Plant Science, 2023)
Introduction Plant pathogens are one of the major constraints on worldwide food production. The antibiotic properties of microbes identified as effective in managing plant pathogens are well documented. Methods Here, we used antagonism experiments and untargeted metabolomics to isolate the potentially antifungal molecules produced by KJ-34. Results KJ-34 is a potential biocontrol bacterium isolated from the rhizosphere soil of rice and can fight multiple fungal pathogens (i.e. Ustilaginoidea virens, Alternaria solani, Fusarium oxysporum, Phytophthora capsica, Corynespora cassiicola). The favoured fermentation conditions are determined and the fermentation broth treatment can significantly inhibit the infection of Magnaporthe oryzae and Botryis cinerea. The fermentation broth suppression ratio is 75% and 82%, respectively. Fermentation broth treatment disrupted the spore germination and led to malformation of hyphae. Additionally, we found that the molecular weight of antifungal products were less than 1000 Da through semipermeable membranes on solid medium assay. To search the potentially antifungal molecules that produce by KJ-34, we used comparative and bioinformatics analyses of fermentation broth before and after optimization by mass spectrometry. Untargeted metabolomics analyses are presumed to have a library of antifungal agents including benzoylstaurosporine, morellin and scopolamine. Discussion These results suggest that KJ-34 produced various biological control agents to suppress multiple phytopathogenic fungi and showed a strong potential in the ecological technologies of prevention and protection.